Strategi Media Informasi Masyarakat Kota Tangerang melalui Akun Instagram @Abouttng - Syanti, Mutiara; Paramita, Sinta (Kiwari, 2024)
The aim of the research carried out is to describe the activities of the Instagram social media account @abouttng as a medium of information for the people of Tangerang City. The research carried out also applied qualitative research and used descriptive analysis methods. A method used to collect research data is applied by processing the data from primary data sources. The results of interviews conducted with the admin of the Instagram account @abouttng are the source of this data, and the research subjects are captions and comments from followers of the Instagram account @abouttng which are relevant to the research objectives. Then there are secondary data sources which are sources of reading material, in the form of books and research results in the form of reports and so on. Tujuan dari penelitian ini yaitu mendeskripsikan aktivitas media sosial Instagram akun @abouttng sebagai media informasi untuk masyarakat Kota Tangerang. Penelitian ini menerapkan jenis penelitian kualitatif serta menggunakan metode analisis deskriptif. Hasil wawancara yang dilakukan dengan admin akun Instagram @abouttng merupakan sumber data ini, dan subjek penelitian adalah caption dan komentar pengikut akun Instagram @abouttng yang relevan dengan tujuan penelitian. Lalu ada sumber data sekunder yang merupakan sumber bahan bacaan, berupa buku-buku dan hasil-hasil penelitian yang berwujud laporan dan lain sebagainya.